Los títeres y su incidencia en la lectura en los niños/as de inicial de 3 a 4 años en la Escuela de Educación Básica Guayaquil, durante el año 2022. - Rodríguez Bajaña., Rosa Lucia (2023)
It has been observed over time that it is very difficult for children to start reading, and this will be a period that parents and teachers will address to the best of their ability. This will be done in different teaching strategies, for example, using puppets with different tones of voices, the children will strengthen their language, they will lose their shyness in class, their voice will be clearer, the teacher will be a very important support in this teaching process In the Guayaquil Basic Education School, the children of Initially from 3 to 4 years old they were the ones who were most interested in the use of puppets, related to the movements that the teacher made, they also tried to imitate her using the puppets. It has been observed that stories, rhymes, poems, strings, tongue twisters, songs and pictograms are didactic resources, leading children to repeat at their workplace, but the use of puppets is even more motivating because it helps them to arouse their curiosity. In which it has been observed that there are communication problems in the family, school and social context, where children during their childhood have not had the motivation to repeat the words in which they have had difficulty in establishing a conversation between them, He has seen that there is a lot of overprotection by parents or grandparents and uncles. The game will play an important role in the learning process, especially in reading, where children will be able to awaken their creativity and imagination.